ANALYSIS OF THE CHALLENGES OF DEVELOPMENT ADMINISTRATION AND E-GOVERNANCE IN NIGERIA: THE EXPERIENCE IN DELTA STATE (Journal of the Management Sciences, 2025)
This paper examines the challenges of development administration and information technology in enhancing service delivery between government and the citizens in Delta State of Nigeria. It argues that while the adoption of information communication has been recommended to be one of the major mechanisms for solving bureaucratic inefficiency, corruption, lack of accountability, and poor communication between the government and its’ citizens, some states in the Nigeria has not adopted this major source of enhancing government performance. The paper utilized questionnaires and focus group meetings research methods to derive its data. The population of the research was 6,742 civil servants in the Delta State of Nigeria government. Data collected were analyzed by using qualitative and quantitative methods. This was done thematically by explaining conceptual issues and the association among variables. The finding reveals that there is a positive correlation between information technology and development administration in the public service sector of Delta State Government in Nigeria. This paper also provides recommendations on the need to appropriate funding and policy changes to enhance the use of modern information technology to galvanize development administration. This is because the adoption of appropriate initiatives could propel more effective communication between government and citizens, and on the one hand, between the public and private sector in Delta State and beyond.
Keywords: Public Infrastructure Project; Information Technology; Development Administration; Public Service Efficiency